2011
DOI: 10.1128/jvi.00879-11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis B Virus Replication by cIAP2 Involves Accelerating the Ubiquitin-Proteasome-Mediated Destruction of Polymerase

Abstract: Cellular inhibitor of apoptosis protein 2 (cIAP2) is a potent suppressor of apoptotic cell death. We have shown previously that cIAP2 is involved in the tumor necrosis factor alpha (TNF-␣)-induced anti-hepatitis B virus (HBV) response; however, the mechanism for this antiviral effect remains unclear. In the present study, we demonstrate that cIAP2 can significantly reduce the levels of HBV DNA replication intermediates but not the total viral RNA or core protein levels. Domain-mapping analysis revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…For instance, MG132 affects hepatitis E virus replication likely through the inhibition of viral transcription and/or translation without a significant effect on cellular translation (Karpe and Meng, 2012). Wang et al (2011) demonstrated that cellular inhibitor of apoptosis protein 2 (cIAP2) can significantly reduce the levels of hepatitis B virus DNA replication via acceleration of the UPS-mediated decay of the polymerase. In the present study, we examined the effects of the proteasome inhibitors MG132 and lactacystin on PCV2 replication and found that the inhibition of the UPS reduces the number of viral DNA copies at 12 hpi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MG132 affects hepatitis E virus replication likely through the inhibition of viral transcription and/or translation without a significant effect on cellular translation (Karpe and Meng, 2012). Wang et al (2011) demonstrated that cellular inhibitor of apoptosis protein 2 (cIAP2) can significantly reduce the levels of hepatitis B virus DNA replication via acceleration of the UPS-mediated decay of the polymerase. In the present study, we examined the effects of the proteasome inhibitors MG132 and lactacystin on PCV2 replication and found that the inhibition of the UPS reduces the number of viral DNA copies at 12 hpi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The following expression plasmids were generously provided: pIFN-␤-Luc (Rongtuan Lin, McGill University, Canada); pEF-STING and p-55C1B-Luc (Takashi Fujita, Kyoto University, Japan); pFlag-MITA, pcDNA3.1-HA-MITA, pFlag-TRIM32, and pFlag-TRIM56 (Hongbing Shu, Wuhan University, China); and pcDNA3.1-CMV-HBV1.1 (Youhua Xie, Fudan University, China), which contains the wildtype HBV 1.1-mer overlength genomic sequence. pHBV1.3, pFlag-Pol (pcDNA3.1-Flag-Pol and pQCXIP-Flag-Pol), the series of truncated mutants of Pol, pcDNA3.1-Flag-Core, pcDNA3.1-Flag-HBx, pcDNA3.1-Flag-Precore, pcDNA3.1-Flag-HBsAg, pFlag-TBK1, pHA-RIG-I, pCMV-Myc-Pol, and pcDNA3-HA-Ub were described previously (10,(26)(27)(28)(29). pHBV1.3-⌬Pol and pCMV-HBV-⌬Pol, defective in viral polymerase expression, were derived from pHBV1.3 and pcDNA3.1-CMV-HBV1.1, respectively, by introducing a frameshift mutation into the Pol gene after codon 108.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants were collected, precleared with protein A/G Plus agarose beads (Santa Cruz) for 30 min, and incubated with anti-Flag or anti-HA antibodies at 4°C. After 2 h, 25 l of a 1:1 slurry of protein A/G Plus agarose beads was added and incubated for additional 2 h. The immunoprecipitates were washed five times with lysis buffer and boiled in 1% (wt/vol) SDS sample buffer, followed by SDS-PAGE and Western blot analysis as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…The UPS is involved in the replication of a broad range of viruses (6). Hindering the activity of the cellular ubiquitin proteasome system, the physiological processes of many viruses are blocked, including invasion by the virus (7), nucleic acid synthesis (8)(9)(10)(11), and the release of virus particles (12). On the other hand, virus infection also affects the host's ubiquitin proteasome system (9).…”
mentioning
confidence: 99%